(untitled) (Journal of Pharmaceutical Negative Results, 2023)
One of the most frequent malocclusion encountered is class II and distalization is considered as a conservative way of treatment. Maxillary molar distalization has been used successfull since long time in orthodontics to correct class II malocclusion. This technique can be used to treat crowding, regain lost arch length, correct deep overbite and correct maxillo-mandibular relationship. Numbers of techniques have been developed to distalize the molars with or without the need of extraction. As a result of over retained deciduous second molars in maxilla the permanent first molars and premolars errupt in a distal position resulting in a class II molar premolar and canine relation.A 13 years old post pubertal male patient having named B_ reported to department of orthodontics and dentofacial orthopaedics with chief complaint of irregularly placed upper & lower front teeth, who was diagnosed with class II subdivision ,having class I molar on left side & class II molar relation on right side and class I canine relation on both side with overjet of 3mm and overbite of 4 mm, crowding of 8mm in upper & 7mm in lower arch, Upper midline is coinciding with lower arch having straight facial profile , 115̊ nasolabial angle ,incompetent lips. Treatment was started with .022 MBT bracket system. Initially levelling and aligning were started with .014 Niti. The modified TPA was placed to start correction from the initial levelling phase. By light coupling force from the modified TPA to the band ensures correction of rotation and correction of crossbite. Two lingual button were place at the palatal surface of the right premolars to derotate them using elastics. A nickel titanium open coil spring was placed between right lateral and first premolar to provide space for the highy placed canine to align. It was necessary to prevent the loss of anchorage, Temporary Anchorage Device were used to control the inclination of upper anteriors.For attainment of molar distalization modified TPA appliance was found to be efficient, non-invasive and non-compliant appliance where 5 mm of distalization was achieved in 3 months and occlusion was settled with class I molar and class I canine relation.